International comparison of urban light rail systems: The role of integrated ticketing, pedestrianistion and population density - Graham Crampton (European Regional Science Association (ERSA), 2002)
The paper presents further results from an international comparative study of urban light rail. Some early findings from this project had been presented at the ERSA2001 conference in Zagreb. Using evidence and visits from 7 countries, 24 different light rail and modern tram systems, some new and some mature, were studied in detail to form conclusions over their overall success and failure. Having computed a 'league table' of relative success based on 6 different ranking indicators, regression analysis was then used to explain the cities' position in the overall ranking. The overall ranking of the system is derived from quantitative evidence on passenger numbers (relative to population) and their growth, both of the light rail system itself and of urban public transport as a whole. Evidence on passenger-km. measures of output is also used. The overall ranking finds that the Swiss and South German urban light rail systems are doing best, with American and British systems doing less well. The econometric estimates of explanations of the ranking positions test the relative importance of three types of independent variables: those describing the physical performance of the light rail system, those describing the way in which the light rail system is marketed, and those summarising the pedestrianisation of the city centre and the population density of the corridors down which the light rail lines run. The most significant variables turn out to be the proportion of passengers using monthly (or longer) travel cards, light rail corridor population density and the relative size of pedestrianisation. The corridor density independent variable had been painstakingly assembled from GIS local area maps of all 24 systems, eventually standardised using MapInfo GIS software. The local area maps can also be used to produce thematic local population density maps, with the light rail lines easily superimposed on another GIS level, so that land use planning conclusions can be discussed for each city. In particular, the corridors of high density which are neglected by current systems become clearer. The overall findings of the report emphasise that the success of light rail and sustainable transport policy in general in Switzerland and South Germany (with the new French systems also performing well) is based more on effective integration and marketing within a compact and car-restrained urban area. Physical features of performance such as speed and vehicle newness were much less important.
Keywords: 330